Fire as friend or foe: the role of scientists in balancing media coverage of fires in National Parks. Issue 1 (2nd January 2022) - Smit, Izak PJ; Joubert, Marina; Smith, Kyle; van Wilgen, Nicola; Strydom, Tercia; Baard, Johan; Herbst, Marna
Abstract : Fire can destroy infrastructure and livelihoods, and claim lives. Yet, fire is inevitable and plays several vital ecological roles that have shaped ecosystems over millennia. Planned fires also serve human needs. Critical media content analysis of 390 media reports (print, online and broadcast) on fires in South African National Parks over a three-year period were used to investigate the portrayal of fire by the mass media. We found a strong emphasis on reactive fire suppression along with a predominantly negative sentiment towards fire (93.9% of total media reach) focussing primarily on losses, destruction and the threat of fires to infrastructure, human health or lives and vegetation. In the few cases where scientists were involved (2.3% of total reach), the narrative, sentiment and images provided a more nuanced perspective of fire as having both detrimental and beneficial consequences (63.6%), imparting key fire ecology concepts to understand fire behaviour better and highlighting the importance of proactive fire-risk reduction measures. Given the influence of the mass media on the views and opinions of the public and policymakers, and its socio-political and management consequences, we conclude that scientists and journalists should do more to engage with one another. We provide pathways and tips to scientists on how to increase their media footprint to promote a more balanced media portrayal of fire. GRAPHICAL ABSTRACT: UF0001